2020
DOI: 10.1177/0300060520966899
|View full text |Cite
|
Sign up to set email alerts
|

Association of D-dimers with acute kidney injury in pregnant women: a retrospective study

Abstract: Objective This study was performed to determine the association of D-dimers measured at the time of admission with the development of acute kidney injury (AKI) in pregnant women. Methods We retrospectively analyzed the data of 625 women who developed AKI and 628 normal pregnant women admitted to our hospital from January 2014 to December 2018. The primary endpoint of the study was the development of AKI in pregnant women, and the secondary endpoint was the development of dialysis and death in women with AKI. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…48 Even for pregnant women, elevated D-dimer is associated with AKI. 43 It can be seen that D-dimer's association with AKI is cross-crowd.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Even for pregnant women, elevated D-dimer is associated with AKI. 43 It can be seen that D-dimer's association with AKI is cross-crowd.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that D-dimer is related to renal insu ciency. [41][42][43][44][45][46][47][48][49][50] Yang et al found that the D-dimer level could predict AKI and mortality in ST-elevated myocardial infarction patients. 41 Guerchicoff also reached a similar conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The laboratory diagnosis of ISTH about DIC includes platelets, D-dimer, fibrin degradation products, FIB, and PT [ 13 ]. It has also been reported that D-dimer as a coagulation-related marker could be used as an effective factor for predicting the occurrence of AKI [ 8 , 9 , 22 ]. In recent years, it was suggested that the D-dimer concentration is likely to rise in the setting of systemic inflammation and infection [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the relationship between ARF and DIC in obstetrics are rare and are nearly all case series 19 , 21 27 . Although Stratta et al 21 , 24 , 28 found that DIC does not have a significant relationship with the severity of renal failure in patients recovering from kidney conditions and although DIC is not directly related to the morphological changes in the kidney 29 , DIC is associated with maternal mortality 30 ; the d -dimer concentration can be used as an independent predictor of PR-AKI 31 , potentially indicating that DIC triggers ARF by provoking the release of cytokines from the endothelium 32 or interacting with the complementary systems 33 , 34 , which are important mechanisms of kidney injury 35 37 , but not by thrombosis in the kidney.…”
Section: Discussionmentioning
confidence: 99%